Long-term performance of 1H, 1H′, 2H, 2H′-perfluorooctyl triethoxysilane (POTS) microcapsule-based self-healing anticorrosive coatings. (January 2014) - Huang, Mingxing; Yang, Jinglei
Self-healing anticorrosive coatings were prepared based on the microencapsulation of 1H, 1H ′, 2H, 2H ′-perfluorooctyl triethoxysilane (POTS). Toluene played a critical role in the successful synthesis of POTS microcapsules although it was not contained in the resultant capsules. The excellent corrosion-resistant property of a POTS microcapsule-modified silicone elastomer coating was demonstrated by a long-term corrosion test, in which the prepared coating was unscratched and exposed to HCl solution for 1 month, and the metal substrate was inspected after peeling off the coating by scanning electron microscopy and energy dispersive X-ray spectroscopy. In addition, the self-healing behavior of a scribed POTS-based epoxy coating was characterized by an electrochemical impedance spectroscopy measurement when the prepared coating was exposed to NaCl solution. The simulated parametric study from electrochemical impedance spectroscopy equivalent circuit demonstrated the process of corrosion-healing kinetics. The anticorrosive mechanism was proposed based on the self-healing functionality of POTS microcapsules.